Detection of Biofilm Formation among the Isolates of Staphylococcus Epidermidis by Modified Microtiter-Plate Test - Haque, N; Bari, MS; Bilkis, L; Hossain, MA; Haque, N; Haque, S; Hasan, MS; Rahman, MA (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Oct;19(4):487-92 The abstract of this article is available on the PubMed website